Anaerobic treatment of chicken manure co-digested with sawdust - Kok, H.Y. (Springer Science and Business Media Deutschland GmbH, 2020)
The high total nitrogen content of chicken manure (CM) makes it suitable to undergo anaerobic digestion (AD) for the production of biogas. In this study, AD of CM was done using sawdust (SD) as co-substrate to investigate the quality of biogas produced. CM and SD were mixed to reach different carbon-to-nitrogen (C/N) ratios of 20, 25, 30, and 35. By using laboratory scale of 10L digesters, biogas production was investigated in anaerobic fermentation. Cow manure, as inoculum, was added in each digester to facilitate the anaerobic fermentation process. The process was performed in batch reactors at temperature of 35Â Â°C, and a retention time of 60Â days. Under mesophilic conditions, all co-digestions of CM and SD improved biogas and methane (CH4) yields significantly compared to control. Percentage of methane had increased up to 65.9 for CM and SD at C/N ratio of 30. The highest methane yields (percentages of methane) obtained from different C/N ratios were as follows: C/N 30 (65.9), C/N 35 (47.0), C/N 20 (46.5) and C/N 25 (44.2). Mono-digestion of CM generated only 20.5 methane on day 60, possibly due to the high amount of nitrogen that caused ammonia inhibition. Â© Springer Nature Singapore Pte Ltd 2020.